Barriers and facilitators in the implementation of a tele-triage system for remote identification of suspected COVID-19 cases by student volunteers - Escobar-Agreda, Stefan (2024)
Introduction. In Peru, the tele-triage system (TTS) led by volunteer students allowed for the remote identification of suspected COVID-19 cases. However, the barriers and facilitators of its implementation are still unknown. Objectives. To describe the barriers and facilitators regarding the implementation of a tele-triage system for the identification of suspected COVID-19 cases in Peru. Methods. A mixed-methods study was developed that described the characteristics of the users who participated in the TTS (quantitative). It also explored the perceptions of users and volunteers regarding the barriers and facilitators of implementing this service (qualitative). Results. Among the 4,317 users evaluated by the TTS, the average age was 36.2 years (standard deviation: 13.2), 58.6% were women, and only 41.4% were classified as suspected cases of COVID-19. Volunteers highlighted that their participation was facilitated by their availability of time and desire to help, although they noted problems with organization and a lack of equipment available for calls. Users valued the emotional support and clarity of the information provided but expressed mistrust about the remote COVID-19 assessment, and a limited understanding of the volunteers’ role. Conclusions. The TTS led by volunteer students allowed for the identification of suspected COVID-19 cases in Peru, and also served as a means to share information. However, aspects of disorganization and a lack of knowledge on the part of users were perceived as barriers to its implementation.